Praktikum 2 Kesejahteraan Sosial UIN Syarif Hidayatullah Jakarta, Mengabdi Untuk Desa Sukamaju, Kecamatan Kadudampit, Sukabumi - Coni Nafiziya Puspasari; Fitriah Sani; Amellia Diah Ayu Fajrihani; Muhammad Afwan Andikha; Syifa Aulia Rr (IKRA-ITH ABDIMAS, 2023)
Practicum 2 Social Welfare activities at UIN Jakarta are carried out in the form of researchand community service in Sukamaju Village. Community service is carried out with severalactivities such as community empowerment in the form of socialization and ecobrick, nonformalteaching assistance carried out in Kindergarten and Elementary Schools as well asthe implementation of activities to commemorate the 77th Indonesian Independence Day in Sukamaju Village. The implementation method in this service begins with the interview andobservation stage which is then used as a guide to produce activities that are carried out for34 days in Sukamaju Village, Kadudampit District, Sukabumi, West Java. The result of nonformalteaching activities is to motivate children to always be eager to receive education andto instill the importance of education for life. The results of the activity from the delivery ofsocialization about ecobrick were quite good and the community gained new knowledgeabout ecobrick, while from the ecobrick community succeeded in sorting organic and nonorganicwaste and could make works such as tables from ecobricks. The result of the August17 celebration activity is a form of success from the practitioner's servant, namely thepractitioner is asked to be a jury and committee for the August 17 competition at RW 003,RW 005, and RW 006 in Sukamaju Village, Kadudampit District, Sukabumi Regency.